A Study of Perceptions and Experiences of Pilgrims Approaching Spiritual Masters in a Religious Mass Gathering "Sinhastha" in Ujjain, MP, India to Explore Relationship of Spirituality and Health - Kirti Deshpande; Rajesh Deshpande; Dattatray N Paliwal (Medsci Publications, 2019)
Introduction: Spirituality and health have been integral parts of all the religions. Religious and Spiritual (R/S) beliefs, influence life- style, attitudes and feelings about life, pain and death. The study conducted to study perceptions and experiences of pilgrims seek- ing health care from spiritual masters in "sinhastha". Methodology: Pilgrims approaching spiritual masters (SM) to seek health care were interviewed using structured questionnaire. Results: Almost all perform religious/spiritual (R/S) activities like prayers and rituals during illness. Health care was sought more for physical than mental health problems. Along with R/S remedies majority pilgrims were taking medical treatment simultaneously. The interventions suggested by SM were drugs, prayers, medita- tion, rituals, fasting, charity work and magical items. The perceived benefits of approaching SM were affection, tolerance, solutions for their problems and feeling close to god. Very few perceive harm from SM. Conclusion: R/S beliefs and practices are important for  people with regard to their health. Health professionals need to incorpo- rate  R/S  background  of  patients  while  planning  management  of health problems as R/S beliefs and practices may be helpful or harmful or may interfere with treatment.